Security in transition(s): The low-level security politics of electric vehicle range anxiety. (December 2019) - Kester, Johannes
By drawing on critical security studies in the context of a sociotechnical transition, this article calls for more attention to the presence and sometimes alternative use of mostly unobserved security practices in the materialization of everyday consumer goods and services. This call is illustrated through a discussion of the phenomenon of range anxiety and the intra-action between drivers of electric vehicles (EVs), designers, and algorithms that observe, estimate and nudge the remaining range of an EV. Inspired by Foucault and Barad, the range-anxiety discussion offers four alternative security insights. First, it supports an argument to include stress as an embodied instance of insecurity. Second, it draws attention to a security apparatus that is based on a constantly expanding assemblage around range estimates. Third, it shows how this apparatus rests on a novel algorithm that has a continuous instead of a binary output and is governed by a distributed sovereignty: where the driver simultaneously is the object of measurement, subject of governance for more efficient driving and the ultimate sovereign who decides on the trip. Lastly, the discussion highlights how range estimates not only mediate the materialization of EVs and their automobility but also (re)perform epistemological or ontological forms of uncertainty.